Estimation of Post-Harvest Losses of Grape Fruit: Evidence from Recent Study in Balochistan - Ullah, Rahmat; Ullah, Hamd; Yousaf, Rabbia; Shehzad, Sikander; Ullah, Kaleem; Ilyas, Muhammad; Rasheed, Mansoor; Liaquat, Ghanha (Journal of Agriculture and Veterinary Science, 2023)
The main objective of this study was to estimate post-harvest losses of grapes and identify their determinants. Cross-sectional data were collected from two main grape-growing districts (Killa Abdullah and Pishin) of Balochistan province, Pakistan. A sample of 180 farmers was drawn from selected areas using multistage sampling techniques and Cochran's proportional allocation techniques. The data were analyzed using the linear multiple regression analysis technique. The study findings showed that post-harvest losses in selected areas ranged from 19% to 29%, and the Killa Abdullah district was found to face relatively more losses. The results of regression analysis showed that socioeconomic factors such as age, education, and experience had a significant negative impact on post-harvest losses, implying that increases in these factors may reduce post-harvest losses. The results further suggest that distance from farm to market increases losses. The average post-harvest losses in the district of Pishin were 227 kg/Ton or 22.72%. Within the respective district, losses ranged from 19% to 27%. The minimum losses were suffered by grapes growers in UC Sheikhalzai whereas the maximum losses occurred in UC Huramzai. In addition, growers who harvest in the morning, use shears/scissors as picking tools, color as maturity indicator, and refrigerated trucks as transport have fewer losses than other growers. However, the losses in the entire surveyed area range from 18% to 28.54%. The least losses suffering UC among all UCs was Sheikhalzai (18.84%) while the most affected UC was Pir Alizai (28.54%) based on the data analysis. It was concluded that the demographics of the operations involved in postharvest management had a large impact on postharvest damage. Based on the results suggested by the study, growers should harvest grapes in the morning using modern picking tools.
Keywords: Fruits and vegetables; Grapes losses; Post-Harvest losses; Pakistan